Fenugreek Seed Extract Prevents Fat Deposition in Monosodium Glutamate (MSG)-Obese Rats - Kumar, P.; Bhandari, U. (Drug Research, 2016)
Aim: To evaluate the preventive effects of an aqueous extract of Trigonella foenum-graecum seeds (AqE-TFG) on fat deposition and dyslipidemia in monosodium glutamate (MSG)-obese rats.Methods: Neonatal male Wistar rats were injected with MSG (4 g/kg b. w., subcutaneously) from day 2 to 14 after birth, on alternate days. From day 43 to 70, MSG treated rats were administered orally with AqE-TFG (0.5 and 1.0 g/kg b. w.). The anthropometric and biochemical parameters were analyzed on day 71.Results: Treatment with AqE-TFG produced significant (P < 0.05 or P < 0.01) reduction in body weight gain, Lee’s index, white adipose tissue (WAT) weights, adiposity index, blood glucose, serum insulin, leptin, lipids (low density lipoprotein cholesterol and very low density lipoprotein cholesterol), cardiac risk indexes (atherogenic index and coronary risk index), and homeostatic model assessment index. AqE-TFG treatment restored the activities of liver and epididymal WAT lipogenic enzymes (fatty acid synthetase and glucose-6-phosphate dehydrogenase) towards normal levels. Histological studies of liver also supported the experimental findings.Conclusion: These findings demonstrated the preventive effect of AqE-TFG on fat deposition and dyslipidemia possibly by improvement in glucose and lipid metabolism, enhancement of insulin sensitivity and down regulation of lipogenic enzymes.
Keywords: adiposity index; Lee’s index; lipogenesis; monosodium glutamate; neonatal; Trigonella foenum-graecum